Non-fungible tokens, tokenization, and ownership - Kaisto, Janne; Juutilainen, Teemu; Kauranen, Joona (Elsevier, 2025)
The emergence of non-fungible tokens (NFTs) in the blockchain environment has prompted many intriguing questions for private law scholars around the world. A question as basic as whether NFTs can be owned has proven difficult in many countries. This is the first research question of our article, which focuses on NFTs created in the Ethereum system by utilizing standard ERC-721. Because these NFTs are identifiable and distinguishable from all other tokens, the notion of owning an NFT is not unthinkable. Yet no universal answer can be offered. Whether NFTs qualify as objects of ownership must be studied at the level of individual legal systems. We argue that NFTs can be owned under Finnish law, with the same probably applying to many other legal systems. Starting with this notion, we pose two further research questions. As the second research question, we ask what problems of a patrimonial law nature may arise in attempts to connect different kinds of rights, even irrevocably, to owning or holding an NFT. Creditor rights seem relatively easy in this respect because most legal systems allow prospective debtors to obligate themselves as they wish. We also study whether a limited liability company could issue an NFT as a share certificate with legal effects corresponding to those of a physical (paper) share certificate. While an affirmative answer could be justified in some legal systems, Finnish law makes it difficult to tokenize a company’s shares other than in the framework of a settlement system within the meaning of the European Union’s DLT Pilot Regulation. Even greater difficulties arise in attempts to connect the ownership of a (material) thing and of an NFT so that a person who owns a token also owns the thing. Our third and final research question addresses tokenization of digital art, which gives rise to some special questions. We ask what rights the transferee of an NFT can receive in connection with tokenization of digital art. Here, our main finding is that digital art can be meaningfully tokenized even though digital copies are not regarded as possible objects of ownership.